Numerical study on fluid-flow characteristics of peristaltic pump. (5th May 2009) - Tatsumi, Kazuya; Matsunaga, Yusaku; Miwa, Yuichi; Nakabe, Kazuyoshi
Flow characteristics in a peristaltic pump, which can be applied to Micro Total Analysis Systems (μ-TAS), were numerically investigated. For the present computational analysis, we assumed a simple sinusoidal wave pattern to simulate the peristaltic motion of flexible channel wall and applied the Immersed Boundary method to the treatment of the wall boundary. The effects of the parameters such as the amplitude and velocity of the peristaltic motion upon the flow characteristics and pump performance were evaluated in the present paper. Saw-toothed or trapezoidal wall patterns were also calculated to examine the potentiality of the pumping flow rate increase.